2020
DOI: 10.17645/mac.v8i2.3217
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus in Spain: Fear of ‘Official’ Fake News Boosts WhatsApp and Alternative Sources

Abstract: The communication of the Coronavirus crisis in Spain has two unexpected components: the rise of the information on social networks, especially WhatsApp, and the consolidation of TV programs on mystery and esotericism. Both have emerged to “tell the truth” in opposition to official sources and public media. For a country with a long history of treating science and the media as properties of the state, this very radical development has surprised communication scholars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 1 publication
1
11
0
8
Order By: Relevance
“…In the Netherlands, this trust is quite high, so it would be interesting to compare the Dutch Covid-19 debate with other (European) countries to track whether the course of these debates has affected the communicative dimensions of trust. Several researchers have already reported their first observations regarding how processes evolved in Spain (Elias & Catalan-Matamoros, 2020), Germany (Wormer, 2020), and Italy (Lovari, 2020). In addition, more comparative and empirical research is needed to investigate how various models of science communication contribute to long-term trust in science and policy-making (Schäfer, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…In the Netherlands, this trust is quite high, so it would be interesting to compare the Dutch Covid-19 debate with other (European) countries to track whether the course of these debates has affected the communicative dimensions of trust. Several researchers have already reported their first observations regarding how processes evolved in Spain (Elias & Catalan-Matamoros, 2020), Germany (Wormer, 2020), and Italy (Lovari, 2020). In addition, more comparative and empirical research is needed to investigate how various models of science communication contribute to long-term trust in science and policy-making (Schäfer, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…This is particularly true if the news was shared on social media by a real-life friend [ 23 ]. The research of Elías and Catalan found that Spanish social media, such as WhatsApp, garnered more public trust than official media sources in COVID-19 pandemic reporting [ 24 ]. However, the increasing use of social media and the presentation of fragmented and false news on social media also lead to the public’s heightened awareness of the source.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Los profesionales de la comunicación han tenido que hacer frente a la dificultad de valorar la situación (Dunwoody, 2020;Catalán-Matamoros, 2020) y, por lo tanto, la presencia de estudios y científicos sanitarios y del área biomédica ha sido importante. Está por ver, si la inclusión de científicos como fuentes autorizadas para valorar los acontecimientos se extiende en el tiempo y a distintos temas, o se trata de tendencia pasajera impuesta por la actual situación marcada por la incertidumbre y la proliferación de noticias falsas sobre la pandemia (Aguado & Bernaola, 2020;Elías, 2020). No obstante, estos datos no hacen más que confirmar la tendencia al alza de los temas médicos (Olvera-Lobo & López Pérez, 2015), una inclinación que algunos autores han descrito como la "medicalización" de las noticias científicas (Bauer, 2003), a pesar de que, en algunos casos estas presenten un componente social y se centren más en los beneficios personales y sociales de la investigación médica, que en las evidencias y características metodológicas de los avances realizados.…”
Section: Conclusionesunclassified